Implementation of Educational Values: Classical vs Contemporary Hadith Interpretation - Wahyu Sihab (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
The purpose of this study is to analyze and compare classical and contemporary approaches to understanding the educational values contained in the hadith, in order to gain a more comprehensive and relevant understanding of Islamic educational practices in the modern era. Educational values in the hadith play a fundamental role in shaping the character and morals of Muslims. The hadith not only serves as a source of religious teachings but also as an ethical guideline in developing students' personalities based on spiritual, social, and moral values. However, differences in historical and social contexts have resulted in two different styles of interpretation. The classical approach tends to emphasize textual understanding and the authenticity of the meaning of the hadith, while the contemporary approach emphasizes the relevance of the teachings of the hadith to the dynamics of modern life and current educational challenges. The research method used is library research by examining various academic sources such as journals, books, articles, and scientific documents related to educational values in the hadith. This approach allows researchers to explore the thoughts of scholars and intellectuals, both from classical and modern perspectives, in a deep and structured manner.